2009
DOI: 10.1186/cc7950
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic epidural anesthesia time-dependently modulates pulmonary endothelial dysfunction in septic rats

Abstract: IntroductionIncreasing evidence indicates that epidural anesthesia improves postoperative pulmonary function. The underlying mechanisms, however, remain to be determined. Because pulmonary nitric oxide has been identified to play a critical role in pulmonary dysfunction in sepsis, we hypothesized that thoracic epidural anesthesia (TEA) modulates endothelial dysfunction via a nitric oxide-dependent pathway.MethodsThirty-six Sprague-Dawley rats underwent sham laparotomy or induction of peritoneal sepsis caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…Interestingly, it was shown in recent studies using the same CLP model that bradykinin-induced pulmonary vasoconstriction was significantly elevated at 6 hours post-induction of peritonitis, indicating a profound endothelial injury. However, in accordance with our current data, the paradoxical bradykinininduced vasoconstriction was not detected 24 hours after induction of CLP-sepsis [18,22]. With the progression of sepsis a recovery from endothelial injury seems highly unlikely.…”
Section: Gadolinium Chloride and Pulmonary Endothelial Dysfunctionsupporting
confidence: 90%
See 2 more Smart Citations
“…Interestingly, it was shown in recent studies using the same CLP model that bradykinin-induced pulmonary vasoconstriction was significantly elevated at 6 hours post-induction of peritonitis, indicating a profound endothelial injury. However, in accordance with our current data, the paradoxical bradykinininduced vasoconstriction was not detected 24 hours after induction of CLP-sepsis [18,22]. With the progression of sepsis a recovery from endothelial injury seems highly unlikely.…”
Section: Gadolinium Chloride and Pulmonary Endothelial Dysfunctionsupporting
confidence: 90%
“…Thereafter, sham laparotomy or induction of CLP-sepsis was performed and the second set of measurements were taken 24 hours post-injury and defined as time point "24 hours." As noted in previous studies [18], the induction of CLP-sepsis was associated with the development of profound tachycardia, tachypnea, leucopenia, and increased serum lactate levels (P < .05 vs. SHAM each and vs. 0 hour measurement within the CLP group; Tables 1 and 2). No significant changes in blood gas analyses, hemoglobin, and hematocrit were detected in septic animals (CLP) compared with sham controls (SHAM) (Tables 2 and 3).…”
Section: Results Of First Series: In-vivo Effects Of Clp-sepsis and Gsupporting
confidence: 73%
See 1 more Smart Citation
“…Subsequent studies reported positive effects of thoracic epidural anaesthesia on pulmonary endothelial capillary integrity in septic rats in the hyperdynamic phase, modulating the production of nitric oxide (effects not found in rats with sepsis in the hypodynamic phase) (26). Authors also reported positive effects on the hepatic microcirculation and inflammatory response in these animals, concluding that in the late phase, cardiac output was not affected, while liver hypoperfusion was reversed (restoring the arterial buffer system mechanisms), and the intrahepatic leukocyte adhesion improved (27).…”
Section: Mutz and Vagtsmentioning
confidence: 99%
“…As an additional parameter for remote injury in the lung, we determined the lung tissue content of MPO, which is a surrogate parameter for inflammatory infiltration by neutrophils [12,13]. Lung tissue specimens (100 lg) were homogenized in 1 ml of 0.05 M potassium-phosphatebuffer (PPS) and hexadecyltrimethylammoniumbromide (HTAB).…”
Section: Lung Tissue Myeloperoxidase (Mpo)mentioning
confidence: 99%